RELIGIOSITY AND BANKING SELECTION CRITERIA AMONG MALAYS IN LEMBAH KLANG - Wan Ahmad, Wan Marhaini (Jurnal Syariah, 2008)
This study examines the role of religiosity in shaping consumer’s choice of banking. Based on an index calculated to measure religiosity, the findings show that there are significant differences between a Muslim’s level of religiosity and Islamic banking as his main choice of bank. The level of religiosity itself is mostly influenced by the Muslim’s formal religious education as well as maturity. For the banking selection criteria, among the Muslims, “availability of ATMs” topped the ranking. Further factor analysis reveals customer and electronic services related factors. Findings suggest that even if Islamic Banking favours well with Muslims in Malaysia, the majority of them still patron conventional banking. And if Islamic bankers want to retain and attract them, the focus should be in developing and expanding their electronic services in order to fulfill their preference for faster and more efficient services.